The specifics of organizing and executing mass sports activities at the university in the 1980s - Kremneva V.N.; Solodovnik E.M. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to compare the content and quality of sports and recreational activities in the Department of Physical Education at PSU in the 1980s and now. Methods and structure of the study. The methods and approaches used to structure and manage sports and recreational activities at PetrSU are examined. Results and conclusions. The research conducted has revealed the highest level of sports and mass activities in the 1980s across all six indicators. Particularly notable are the number of mass discharges as a percentage of the student population, the performance of the VSO, the number of gold TRP badges awarded, the training of instructors and judges among students, and the currently lost indicator — «Agitation and Propaganda». Based on the «Spartakiad» indicator alone, an increase in sports participation in modern mass sports activities can be observed. Looking back at the historical legacy, drawing on the accumulated experience, and conducting a thorough analysis will assist in identifying the most effective practices for organizing mass sports activities that can be employed (with appropriate modern adaptations) in the present day.